Reasoning patterns and modes of prospective biology teachers on embryology learning with TPACK framework - Nia Nurdiani; Nuryani Y. Rustaman; Wawan Setiawan; Didik Priyandoko (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
The study was aimed at determining the effectiveness of learning using TPACK (Technological Pedagogical and Content Knowledge) framework in helping the change of reasoning patterns and modes of Biology prospective teachers so that it facilitates in encompassing the Embryology as one of abstract concepts. The subjects used were 49 students of Biology teachers who were having a contract in Embryology course in Biology Education Study Program, in a private educational institute in Bandung. The research design used was quasi-experimental with time-series design type.  The measurement of the level of reasoning ability, patterns, and modes of the students were done through the Test of Logical Thinking (ToLT) three times (before the learning program takes place, after learning the first four main subjects, and after the learning program was over). The results showed that the Embryology learning with TPACK framework could directly change the from concrete and transitional reasoners categories to formal reasoners. The learning with TPACK framework also influenced the shift of the students’ logical thinking modes; from the ownership of proportional and/or correlational mode to the ownership of two or three reasoning modes between proportional, probability, correlational, and combinatorial, except the variable control mode.